2019
DOI: 10.1155/2019/6704031
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Appendage Occlusion in High Bleeding Risk Patients

Abstract: Objectives. The aim of this study was to investigate the outcomes of left atrial appendage occlusion (LAAO) in high bleeding risk patients suffering atrial fibrillation (AF) and to analyze the different antithrombotic therapies following the intervention. Background. Methods. This monocentric study included 68 patients with nonvalvular AF with an absolute contraindication to OAT or at high bleeding risk. Follow-up was done with a clinical visit at 3-6-12 months. Results. Successful LAAO was achieved in 67/68 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The therapeutic attitude shown in our study is similar to that reported in non-CKD patients [22], however the excess of early bleeding should lead us to reconsider whether it is really necessary, in patients with such a high risk of bleeding, to take two drugs rather than one after the procedure.In fact, there are many doubts about the use of dual antiplatelet agents in dialysis patient even in the presence of other clinical situations, such as ischemic heart disease [23]. Recently, even among cardiologists, the need to always prescribe double antiplatelet therapy after LAA occlusion has been questioned, and several registry data suggest that single antiplatelet therapy is just as effective as double antiplatelet therapy [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic attitude shown in our study is similar to that reported in non-CKD patients [22], however the excess of early bleeding should lead us to reconsider whether it is really necessary, in patients with such a high risk of bleeding, to take two drugs rather than one after the procedure.In fact, there are many doubts about the use of dual antiplatelet agents in dialysis patient even in the presence of other clinical situations, such as ischemic heart disease [23]. Recently, even among cardiologists, the need to always prescribe double antiplatelet therapy after LAA occlusion has been questioned, and several registry data suggest that single antiplatelet therapy is just as effective as double antiplatelet therapy [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…This reduces the risk of bleeding, and demonstrates that after successful LAAC patients would likely enjoy much lower risk of bleeding than being on warfarin postclosure. This is particularly enticing for those patients who are traditionally considered to be a high risk for bleeding with anticoagulants in combination with antiplatelet medications 85 86…”
Section: Discussionmentioning
confidence: 99%
“…While current guidelines recommend the use of triple therapy including an oral anticoagulant, P2Y12 inhibitor and aspirin in such patients,9 80 this approach has been questioned by a number of randomized controlled trials that demonstrated lower risk of major bleeding with no change in incidence of ischemic events in patients treated with a variety of alternative drug regimens 81-84. This bleeding risk is enhanced in certain clinical situations where use of dual antiplatelet medications alone rather than triple therapy could potentially lower the bleeding risk substantially 85 86…”
Section: Bleeding Risk With Anticoagulation In Afibmentioning
confidence: 99%
“…Currently, LAAC is performed widely for antithrombotic events prevention in NAVF patients with heart failure, chronic kidney disease and high bleeding risk [10][11][12]. Moreover, in NVAF patients with PCI who may require both OAC and antiplatelet therapy, LAAC may have the potential bene t by reducing the usage of OAC.…”
Section: Introductionmentioning
confidence: 99%